Narayan As a Social Novelist-In Swami and Friends: Exploring the Social Realities of Traditional India through Swami and Friends (Journal of Advances and Scholarly Researches in Allied Education, 2013)
R. K. Narayan’s Swami And Friends is a novel writtenin a socio-economic context when India was still a tradition based country. RKNarayan started his prolific writing career with this novel written in 1935.Set in the fictional town of Malgudi, Swami and Friends is the story of a youngmischievous suburban kid. It is full of humor and irony. Despite this, it tooktime for the budding writer to be acknowledged as an author. Fortunately forhim, he had help from many quarters, such as the well-established Britishauthor Graham Green. He called Swami and Friends a work of remarkable maturity."There are writers—Tolstoy and Henry James to name two—whom we hold inawe, writers—Turgenev and Chekhov—for whom we feel a personal affection, otherwriters whom we respect—Conrad for example—but who hold us at a long arm'slength with their 'courtly foreign grace.' Narayan (whom I don't hesitate toname in such a context) more than any of them wakes in me a spring ofgratitude, for he has offered me a second home. Without him I could never haveknown what it is like to be Indian."—Graham Greene